2018
DOI: 10.1016/j.jcomdis.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Speech outcomes following Sommerlad primary palatoplasty: Results of the Ghent University Hospital

Abstract: Patients still present with both obligatory and compensatory speech disorders following Sommerlad's palatoplasty. In the future, a Dutch speech assessment protocol will be developed in order to standardize follow-up of these patients and to allow for within-center and inter-center comparisons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 40 publications
0
21
2
Order By: Relevance
“…Percent consonant correct (PCC) was used to report articulation outcomes, with 88.7 PCC reported for this group. Bruneel et al (2018) also reported outcomes in a small cohort (n = 16), with a similar mean age of palate repair at 12 months of age to the Klinto et al (2018) study, although with a much wider range of 7 to 25 months. Fifty-six percent were reported to have acceptable speech at age 5.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…Percent consonant correct (PCC) was used to report articulation outcomes, with 88.7 PCC reported for this group. Bruneel et al (2018) also reported outcomes in a small cohort (n = 16), with a similar mean age of palate repair at 12 months of age to the Klinto et al (2018) study, although with a much wider range of 7 to 25 months. Fifty-six percent were reported to have acceptable speech at age 5.…”
Section: Introductionmentioning
confidence: 78%
“…When comparing these outcomes to those studies reporting the Sommerlad technique with a robust speech methodology at 5 years of age (Cairns et al, 2014;Klinto et al, 2018;Bruneel et al, 2018;Mapar et al, 2019;Nyberg et al, 2018) in 4 of the 5 studies, surgery was undertaken between a mean age of 11.3 to 13.6 months, compared with a mean age of 6.6 months in this study. Only the study by Cairns et al (2014) had a similar age at palate repair to this study.…”
Section: Comparison With Other "Sommerlad Technique" Studiesmentioning
confidence: 96%
See 3 more Smart Citations